2022
DOI: 10.1098/rsif.2022.0088
|View full text |Cite
|
Sign up to set email alerts
|

Critical roles for EGFR and EGFR–HER2 clusters in EGF binding of SW620 human carcinoma cells

Abstract: Epidermal growth factor (EGF) signalling regulates normal epithelial and other cell growth, with EGF receptor (EGFR) overexpression reported in many cancers. However, the role of EGFR clusters in cancer and their dependence on EGF binding is unclear. We present novel single-molecule total internal reflection fluorescence microscopy of (i) EGF and EGFR in living cancer cells, (ii) the action of anti-cancer drugs that separately target EGFR and human EGFR2 (HER2) on these cells and (iii) EGFR–HER2 interactions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 85 publications
(101 reference statements)
2
13
1
Order By: Relevance
“…In a recent report, Wollman analyzed the dynamics and clustering of EGFR and HER2 on a carcinoma cell line SW620 using total internal reflection fluorescence (TIRF) microscopy with fluorescently labeled receptors and ligand. 57 Consistent with previous studies, they observed preformed EGFR clusters (peak size∼ 6 receptors/cluster, range 2−90); somewhat surprisingly, they did not observe EGFR monomers. However, the kinetics of movement within the clusters suggested that the EGFR consisted of loosely bound monomers and dimers rather than tightly bound oligomers.…”
Section: And Functionssupporting
confidence: 89%
See 1 more Smart Citation
“…In a recent report, Wollman analyzed the dynamics and clustering of EGFR and HER2 on a carcinoma cell line SW620 using total internal reflection fluorescence (TIRF) microscopy with fluorescently labeled receptors and ligand. 57 Consistent with previous studies, they observed preformed EGFR clusters (peak size∼ 6 receptors/cluster, range 2−90); somewhat surprisingly, they did not observe EGFR monomers. However, the kinetics of movement within the clusters suggested that the EGFR consisted of loosely bound monomers and dimers rather than tightly bound oligomers.…”
Section: And Functionssupporting
confidence: 89%
“…However, oligomers of EGFR and other family members pre-exist on the membrane (in an inactive state), so there must be other mechanisms influencing kinase activation. In a recent report, Wollman analyzed the dynamics and clustering of EGFR and HER2 on a carcinoma cell line SW620 using total internal reflection fluorescence (TIRF) microscopy with fluorescently labeled receptors and ligand . Consistent with previous studies, they observed preformed EGFR clusters (peak size∼ 6 receptors/cluster, range 2–90); somewhat surprisingly, they did not observe EGFR monomers.…”
Section: Egf/egfr Families: Structures Oligomers and Functionssupporting
confidence: 64%
“…From these quantitative images, we identify diffraction-limited local intensity maxima (we denote these as foci —see table 1 for a description of technical slimfield microscopy nomenclature used in this study) to a lateral spatial precision of 40 nm [ 36 ]. Slimfield uses ∼millisecond sampling that is sufficiently rapid to link the moving foci derived from the same emitter sources over sequential image frames, following appropriate bespoke particle tracking analysis [ 33 , 37 , 38 ], into tracks . Each of these tracks implies the presence of a particle containing one or more associated molecules; typically more than one prior to photobleaching, so more generally, we term each a molecular assembly .…”
Section: Introductionmentioning
confidence: 99%
“…The Slimfield microscope (without alteration for PaTCH acquisition) is based on a custom-built epifluorescence/TIRF optical pathway previously described (Payne-Dwyer and Leake, 2021; Plank et al, 2009; Syeda et al, 2019). An optimised angle of excitation beam delivery distinguishes PaTCH imaging from the traditionally used TIRF and HILO microscope settings, thereby facilitating the imaging of transmembrane proteins in mammalian cells (Wollman et al, 2021)In this study the angle of incidence of the excitation beam was set to a sub-critical angle of 55° by translation of a telescope lens, as calibrated using the lateral displacement of the beam downstream of the focal plane (Dresser et al, 2021). At this angle, we estimated that roughly 30% of the incident light is coupled into a reflected TIRF mode, with the associated enhancement of the excitation field at the surface.…”
Section: Methodsmentioning
confidence: 99%
“…Utilising novel PaTCH microscopy to study this newly developed cell line, we were able to confirm the collection of CCR5 into small puncta and track the fluorescent intensity of these assemblies through time as they decayed due to photobleaching. Using this data and the method utilised in previous studies (Jin et al, 2021;Leake et al, 2006Leake et al, , 2008Reyes-Lamothe et al, 2010;Syeda et al, 2019;Wollman et al, 2021Wollman et al, , 2020b we were able to determine the stoichiometries of individual CCR5 assemblies and form stoichiometry distributions for individual cell populations. We found that the distribution of CCR5 stoichiometries exhibits a significant range and can be characterised by the existence of periodic peaks in stoichiometry with an average interval of 2.27 ± 0.47 molecules.…”
Section: Patch Microscopy Investigations Of Ccr5mentioning
confidence: 99%